Alguns aspectos da avaliação estética da face - Gonçalves, MA (1993)
On planning an orthodontic treatment is very important to analyse the soft tissues that covers the dental and bone structure especially because we can achieve better results in the facial esthetic and although in the perioral function and for the stability of the treatment. The study of all these factors is going to define the best spacial position of the incisors and consequently of all denture.